Does acute alcohol intoxication interfere with colonic anastomosis wound healing? : a rat model of nondestructive colon trauma - Morais, Pedro Henrique Alves de (2013)
PURPOSE: To evaluate the effects of acute alcohol intoxication on healing of colonic anastomosis. METHODS: Thirty-six rats were allocated into two groups. Animals in the alcohol (A) were given 2 mL of ethanol diluted in 0.9% saline solution to a concentration of 40% by gavage immediately before anesthesia, whereas control (C) animals received 2 mL of 0.9% saline solution via the same route. A colonic anastomosis was then performed in all animals. On postoperative days 1, 3, and 7, anastomotic breaking strength was assessed and histopathological examination was performed. Change in body weight and mortality were also evaluated. RESULTS: The median of anastomotic tensile strength on the postoperative day 1 was 0.09 Newtons for group A and 0.13 for group C. (p>0.05). The median of anastomotic tensile strength on the postoperative day 3 was 0.13 Newtons for group A and 0.17 for group C. (p>0.05). The median of anastomotic tensile strength on the postoperative day 7 was 0.30 Newtons for group A and 0.35 for group C. (p>0.05). There was no significant difference between the groups A and C, in the first, third or seventh POD (p>0.05), in any of the analyzed parameters. There were no statistical differences between groups in the weight. Three animals died, all from the group A. CONCLUSION: Acute alcohol intoxication did not interfere with wound healing of colonic anastomoses, although it caused early postoperative mortality.